Application of response surface methodology for the optimisation of micro friction surfacing process - Vitanov, V. I.; Javaid, N.; Stephenson, David J. (Elsevier Science B.V., Amsterdam., 2010)
The aim of this work is to identify relationships between the input variables and the process response and to develop predictive models that can be used in the design of new friction surfacing applications. Moreover to investigate the use of standard CNC machines for friction surfacing. The experimental design techniques and response surface methodology were used to investigate and select the combination of factor levels that produced the optimal response. The main effect of the velocity ratio obtained by dividing the feed rate of mechtrode with traverse rate of substrate was observed to be the most significant factor on the process response. Based on the results of optimisation it was observed that the lower to intermediate levels of rotational speed and intermediate to higher levels of velocity ratio produced good coating quality. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Friction surfacing Factorial design Response surface methodology Optimisation